2012
DOI: 10.1590/s0100-06832012000400004
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade e correlação espacial de micronutrientes e matéria orgânica do solo com a produtividade da pimenta-do-reino

Abstract: RESUMOEstudos que visem elucidar a variação espacial de atributos de solo associada à resposta de produção das lavouras podem contribuir para a aplicação racional de insumos, possibilitando ganhos econômicos e ambientais. Objetivou-se neste trabalho avaliar a variabilidade espacial dos micronutrientes Fe, Cu, Zn e Mn e da matéria orgânica, bem como sua correlação espacial com a produtividade de uma lavoura de pimenta-do-reino cultivada em um Latossolo Vermelho-Amarelo distrófico. O estudo foi realizado em uma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
2
0
4
Order By: Relevance
“…Regarding micronutrients, there was a significant negative correlation for Fe in the Xaraés forage, p <0.01 between Fe and TGM, and p <0.05 between the same micronutrient and TDM and DMAR (Table 6). Gontijo et al (2012), when evaluating the productivity of another crop also observed a significant negative correlation between the Fe content in the soil and productivity, attributing this effect to the high content of this element in the soil, as observed in the present study. The same authors reported that excess Fe promotes its excessive absorption, causing nutritional imbalance which can lead to production losses.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding micronutrients, there was a significant negative correlation for Fe in the Xaraés forage, p <0.01 between Fe and TGM, and p <0.05 between the same micronutrient and TDM and DMAR (Table 6). Gontijo et al (2012), when evaluating the productivity of another crop also observed a significant negative correlation between the Fe content in the soil and productivity, attributing this effect to the high content of this element in the soil, as observed in the present study. The same authors reported that excess Fe promotes its excessive absorption, causing nutritional imbalance which can lead to production losses.…”
Section: Resultssupporting
confidence: 87%
“…The high Fe content may be associated with the soil source material, because high Fe levels are common in soils of the region. Gontijo et al (2012) also attribute the high Fe content observed to the source material and complemented that this Fe concentration causes the gradual loss by lixiviation of other elements. A similar result for N was observed for Mn, which although it was one of the most absorbed nutrients showed no significant correlation.…”
Section: Resultsmentioning
confidence: 63%
“…Sendo assim, as informações relacionadas com os valores dos ramos produtivos minimiza a variação espacial da produtividade, proporcionando maior continuidade espacial. Segundo Gontijo et al (2012), variáveis que apresentam maiores alcances de dependência espacial tendem a se apresentarem mais homogêneas, espacialmente, na área.…”
Section: Resultsunclassified
“…O modelo esférico foi o que melhor se ajustou aos semivariogramas para todos os atributos químicos. Resultados semelhantes foram encontrados por Gontijo et al (2012) …”
Section: Resultsunclassified